Práticas sociais : outras formas de ser artista - Moreira, Piatan Lube (2016)
We write Art to a new level and creative relation, recently highlighted its refined methodologies of action and reception: relational, participatory, community, social, anti-marketing and cross-disciplinary. We have as raw original research the cooperatio